Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208681
|View full text |Cite
|
Sign up to set email alerts
|

Online gaming motivations scale

Abstract: Understanding gaming motivations is important given the growing trend of incorporating game-based mechanisms in non-gaming applications. In this paper, we describe the development and validation of an online gaming motivations scale based on a 3-factor model. Data from 2,071 US participants and 645 Hong Kong and Taiwan participants is used to provide a cross-cultural validation of the developed scale. Analysis of actual in-game behavioral metrics is also provided to demonstrate predictive validity of the scale. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 6 publications
2
98
0
7
Order By: Relevance
“…Based on a factor analysis of questions inspired by the original Bartle's player types, Yee [42,44] identified three main components of player motivation with ten sub-components: achievement (advancement, mechanics, competition), social (socializing, relationship, teamwork), and immersion (discovery, roleplaying, customization, escapism). More recently, Yee [43] expanded on his previous work by conducting a factor analysis with over 140,000 participants and developed a 'gamer motivation profile' composed of 12 dimensions grouped in 6 clusters: action (destruction and excitement), social (competition and community), mastery (challenge and strategy), achievement (competition and power), immersion (fantasy and story), and creativity (design and discovery).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a factor analysis of questions inspired by the original Bartle's player types, Yee [42,44] identified three main components of player motivation with ten sub-components: achievement (advancement, mechanics, competition), social (socializing, relationship, teamwork), and immersion (discovery, roleplaying, customization, escapism). More recently, Yee [43] expanded on his previous work by conducting a factor analysis with over 140,000 participants and developed a 'gamer motivation profile' composed of 12 dimensions grouped in 6 clusters: action (destruction and excitement), social (competition and community), mastery (challenge and strategy), achievement (competition and power), immersion (fantasy and story), and creativity (design and discovery).…”
Section: Related Workmentioning
confidence: 99%
“…Research on gameplay motivations has shown that players have diverse personal preferences regarding how and what they play [20,33,44]. Researchers have developed player type models [20,27] or gamer motivation scales [43,44] to capture the diverse styles of play exhibited by different players.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobre esse aspecto, destaca-se que, apesar do modelo identifi car três grandes fatores, os 39 itens que compõem a versão original da escala avaliavam os dez componentes adjacentes, sem proporcionar um meio direto de avaliar seus fatores. Ademais, a ausência de estudos fora do contexto amostral com participantes de língua inglesa não asseguram evidências conclusivas sobre a validade da estrutura fatorial em outros contextos culturais (Yee et al, 2012).…”
Section: Motivações Para Jogos Onlineunclassified
“…Frente ao anteriormente descrito, Yee et al (2012) elaboraram a Escala de Motivações para Jogos Online, que consiste em uma versão reduzida de seu instrumento original (Yee, 2006). A versão ora apresentada é composta por 12 itens distribuídos nos fatores teorizados: realização, social e imersão.…”
Section: Escala De Motivações Para Jogos Onlineunclassified